Evaluation of LigB polymerase chain reaction as a complementary tool to microscopic agglutination test for the detection of bovine leptospirosis in serum samples - Saraullo, Vanina Rosa; Hamer, Micaela; Esteban, Micaela; Sanchez, Maria Cristina; Brihuega, Bibiana Felicitas; Martinez, Mara Leila (Elsevier, 2025)
Leptospirosis is a significant infectious disease affecting livestock. Microscopic agglutination test (MAT) is used as the gold standard; however, the inclusion of molecular tools (PCR) could improve the accuracy of diagnosis. We evaluated the combination of MAT and a LigB-PCR in bovine serum to detect positive cases in animals clinically suspected of leptospirosis. 127 samples were classified by MAT (cut-off 1:100). Of 45 negative samples negative by MAT, 42.2 % were positive by PCR. In addition, the number of confirmed cases of bovine leptospirosis based on clinical suspicion and MAT and/or PCR increased the diagnostic rate to 79.5 %. LigB-PCR can detect traces of leptospiral DNA in serum with negative or low antibody titers and could be used as a complementary tool to MAT.